The knowledge economy and lifelong learning: a critical reader - Livingstone, D. W.; Guile, David (Boston Sense Publishers, 2012)
"This book presents some of the most trenchant critical analyses of the widespread claims for the recent emergence of a knowledge economy and the attendant need for greater lifelong learning. The book contains two sections: first, general critiques of the limits of current notions of a knowledge economy and required adult learning, in terms of historical comparisons, socio-political construction and current empirical evidence; secondly, specific challenges to presumed relations between work requirements and learning through case studies in diverse current workplaces that document richer learning processes than knowledge economy advocates intimate. Many of the leading authors in the field are represented. There are no other books to date that both critically assess the limits of the notion of the knowledge economy and examine closely the relation of workplace restructuring to lifelong learning beyond the confines of formal higher education and related educational policies. This reader provides a distinctive overview for future studies of relations between work and learning in contemporary societies beyond caricatures of the knowledge economy. The book should be of interest to students following undergraduate or postgraduate courses in most social sciences and education, business and labour studies departments, as well as to policy makers and the general public concerned about economic change and lifelong learning issues. D. W. Livingstone is Canada Research Chair in Lifelong Learning and Work and Professor Emeritus at the Ontario Institute for Studies in Education, University of Toronto. David Guile is Professor of Education and Work at the Institute of Education, University of London." (Publisher's page)
Section One. General critiques -- 1. Beyond the hype: intellectual property and the knowledge society/knowledge economy / Kenneth Carlaw, Les Oxley, Paul Walker, David Thorns and Michael Nuth -- 2. Mapping knowledge in work: proxies or practices? / Chris Warhurst and Paul Thompson -- 3. A Cultural political economy of competitiveness: And its implications for higher education / Bob Jessop -- 4. Debunking the 'knowledge economy': the limits of human capital theory / D. W. Livingstone -- 5. Globalization, knowledge, and the myth of the magnet economy / Phillip Brown and Hugh Lauder -- 6. 'The Art of knowing': social and tacit dimensions of knowledge and the limits of the community of practice / Paul Duguid -- 7. The Knowledge economy: education, work, and the struggle to (Re-)regulate the distinction between 'necessary' and 'free' labour time / Peter Kennedy -- Section Two. Specific challenges -- 8. Creating and using knowledge: an analysis of the differentiated nature of workplace learning environments / Alison Fuller, Lorna Unwin, Alan Felstead, Nick Jewson and Konstantinos Kakavelakis -- 9. Professions as knowledge cultures / Monika Nerland -- 10. Object lessons: workplace artifacts as representations of occupational Jurisdiction / Beth A. Bechky -- 11. Improving work processes by making the invisible visible / Arthur Bakker, Celia Hoyles, Phillip Kent and Richard Noss -- 12. Divergent working and learning trajectories in social services: insights from a use-value perspective / Peter H. Sawchuk -- 13. Working and learning in the 'knowledgebased' creative and cultural sector: vocational practice, social capital, and entrepreneurability / David Guile -- 14. The Learning worker, organizations and democracy / Catherine Casey -- 15. Education, globalization and The 'voice of knowledge'1 / Michael Young.
includes bibliographical references.
Keywords: Adult education; ADULT EDUCATION; CONTINUING EDUCATION; LEARNING; KNOWLEDGE